2-Chloro-3-nitropyridine - Ng, S.W. (International Union of Crystallography, 2010)
In the title compound, C(5)H(3)ClN(2)O(2), the nitro group is twisted by 38.5 (2)degrees with respect to the pyridine ring. In the crystal, adjacent molecules are linked by non-classical C-H center dot center dot center dot N and C-H center dot center dot center dot O hydrogen bonds, forming a layer motif.